Socio-cognitive mindfulness is a well-being booster: A serial mediation model to test the mindfulness reappraisal hypothesis with managers - Junça Silva, A. (Evidence-based HRM, 2025)
Purpose The purpose of this study was to investigate the relationship between mindfulness and two types of well-being, namely subjective and psychological well-being, particularly in a managerial context. The mindfulness-to-meaning theory (MMT) suggests that the practice of mindfulness might lead individuals to reevaluate and find greater meaning in their experiences, ultimately contributing to increased well-being. Accordingly, we argue that mindfulness boosts well-being because it may potentially lead managers to reappraise what surrounds them, making them experience more frequent positive affect. Design/methodology/approach A two-wave survey with a two-week interval was used to gather quantitative data. An overall sample of 1,260 managers with and without experience with mindfulness took part in the study. Findings Structural equation modeling showed that mindfulness had a direct and positive relationship with both subjective and psychological well-being. Furthermore, both processes – positive reappraisal and positive affect – mediated the path from mindfulness to both forms of well-being. Practical implications The findings emphasize the importance of creating training strategies that develop managers’ ability to positively reappraise daily events and occurrences, which may trigger more frequently positive affective experiences. Therefore, promoting mindfulness training at the workplace may develop mindful employees, especially by working on specific strategies, such as positive reappraisal, which may be a promising empirical-based strategy to enhance well-being. Originality/value This study adds knowledge about how mindfulness can contribute to well-being and contributes to expanding the mindfulness-to-meaning theory by adding positive affective experiences as an additional mechanism in the relationship between mindfulness and well-being. Specifically, it demonstrates that the practice of mindfulness helps managers to positively reappraise their surroundings, which results in more frequent experiences of positive affect.